Strategies for implementing music‐based interventions for people with dementia in long‐term care facilities: A systematic review. (19th October 2021) - Amano, Takashi; Hooley, Cole; Strong, Joe; Inoue, Megumi
Abstract: Objectives: Research has found that music‐based interventions can decrease behavioral and psychological symptoms of dementia or behaviors that challenge (BPSD/BtC). However, how to effectively implement these interventions is unclear. This study synthesizes available evidence regarding implementation strategies and outcomes of music‐based interventions for people with dementia at residential long‐term care facilities. Methods: Study registered with PROSPERO (registration number: CRD42020194354). We searched the following databases: PsychInfo, PubMed, MEDLINE, CINAHL, and The Cochrane Library. Inclusion criteria included articles targeting music‐based interventions conducted for people with dementia, studies conducted in residential long‐term care facilities, and articles that reported implementation strategies and outcomes of the intervention. Results: Of the included eight studies, half were studies of music therapy and the other half were on individualized music. 49 implementation strategies were reported. The most frequently reported category of strategies was planning (34.7%), followed by education (24.5%), quality management (24.5%), restructuring (12.2%), and finance (4.1%). No strategies under the category of attending to the policy context were reported. The most frequently reported implementation outcomes were appropriateness (27.3%), followed by adoption (22.7%), fidelity (22.7%), acceptability (9.1%), sustainability (9.1%), and cost (9.1%). No studies measured feasibility or penetration. Conclusions: Although various effective implementation strategies were identified, we were unable to examine the effectiveness of individual implementation strategies due to the designs of the selected studies. Less attention has been paid to strategies that aim at structural changes of intervention delivery systems. Future studies should investigate facilitators and barriers of implementing music‐based interventions especially focusing on structural aspects. Key points: Although previous studies have shown music‐based interventions are effective at improving various outcomes of dementia in long‐term care facilities, implementing them can be challenging. Various effective implementation strategies have been utilized in previous studies. Designs of selected studies preclude from assessing which implementation strategy is the most effective. There is a paucity of research on our setting strategies that aim to influence the behavior of intervention delivery systems (e.g., external policy, incentives).